ANALISIS EFEKTIVITAS LAYANAN SIMADU DALAM MENINGKATKAN MUTU PELAYANAN PUBLIK DI ULT BPMP PROVINSI KALIMANTAN TENGAH - Triwid Syafarotun Najah; Cindy Marcellina Putri (STKIP Pesisir Selatan, 2025)
This study aims to analyze the effectiveness of the Integrated Service Unit Information System (SIMADU) in improving the quality of public services at the Central Kalimantan Provincial BPMP. The approach used is qualitative with a field study method to assess the effectiveness of SIMADU based on five dimensions of service quality within the SERVQUAL framework. Data were collected through in-depth interviews with the ULT Coordinator, statistical analysis of SIMADU data for the period 2018–2025, results of the Community Satisfaction Survey, and a review of operational standard documents. The analysis was conducted using a qualitative descriptive method with triangulation of sources. The results of the study show that SIMADU has proven to be very effective, with a service completion rate of 100% of a total of 1,956 requests and a Community Satisfaction Index of 92.74% in the “Very Good” category. This system provides 24-hour digital services with adaptive multi-channel access, covering all 14 districts/cities, where 63.3% of users are teachers. The novelty of the research lies in the comprehensive evaluation of e-government-based information systems at the provincial level using the SERVQUAL approach over a seven-year period (2018–2025), which resulted in a hybrid strategy model (digital and face-to-face) as a form of inclusive digital transformation that has the potential to be replicated by other education quality assurance institutions in Indonesia.